Konsep Kesederhanaan Tari Renteng di Desa Saren, Nusa Penida, Klungkung, Bali - Anak Agung Gde Agung Indrawan (Gelar : Jurnal Seni Budaya, 2020)
The Renteng dance is a group dance that is held and only taken by adult women in Saren Village, Nusa Penida, Klungkung, Bali. This dance movement is multiyear and repetitive, and the presentation, clothing and musical accompaniment is very simple. The simplicity of the form and presentation of Renteng gives rise to the beauty that provides the formalistic aesthetic experience of this dance. However, the form of a formalistic aesthetic experience has not many people understand it. The focus of the problem in this study was how the concept of simplicity in the Renteng dance in Saren village. The research discusses the concept of simplicity in the Renteng dance which can create a formalistic aesthetic experience. The purpose of this research is to obtain a conceptual depiction of this dance based on the simplicity of its shape. This type of research is descriptive-analytic using non-participant observation methods, interviews, and documentation. The results of this study, that the concept of simplicity on the Renteng dance consisted of the simplicity of the element, the simplicity of the structure, and the simplicity of the technique. The conclusion is first, the concept of simplicity of elements or elements on the Renteng dance is the simplicity of the composition of the elements contained in this dance, which includes motion, floor design, and top design, fashion, and musical accompaniment; Second, the concept of the simplicity of the Renteng dance structure is a draft whose application is composed through simple motion and repetitive patterns; Thirdly, the concept of the simplicity of the Renteng dance technique is achieved through simple means with low or uncomplicated complexity making it easy to be extracted.